ChemInform Abstract: Tetrabutylammonium Bromide Catalyzed Tandem Addition/Cyclization of o‐Aralkynylaryl Aldehydes with Trimethyl(trifluoromethyl)silane: Synthesis of Trifluoromethyl Group Containing Phthalans. Issue 16 (22nd April 2014) - Hu, Bo‐Lun; Li, Chun‐Lin; Liao, Zhi‐Yong; Zhang, Xing‐Guo
Abstract The regio‐ and stereospecific reaction shows good functional group tolerance and provides (Z)‐1‐alkylidene‐3‐(trifluoromethyl)phthalans in moderate to excellent yields.